Larval development of the bamboo borer (Dinoderus minutus Fabricius) using individual rearing method - Abood, Faizah; Norhisham, Ahmad R. (Universiti Putra Malaysia Press, 2013)
Detailed information on larval development of the powder-post beetle, Dinoderus minutus, was investigated using individual rearing method under laboratory conditions at 27±2°C and 75±5% relative humidity. Five classes of head capsules were recorded, indicating five moults from first instar to prepupa. The mean larval duration recorded was 52.8±0.31 days with 8.04±0.12 days for the first instar larva, followed by 9.74±0.20 days, 13.10±0.17 days, 16.20±0.15 days and 5.72±0.13 days, for the second to fifth instar larvae, respectively. The longest instar stage was the fourth instar, with a development time ranging from 14 to 18 days and the shortest was the fifth instar ranging from 4 to 6 days. The highest growth ratio of larva by body weight was 2.70, which was observed between the first and second instars. This indicated that the maximum feeding rate of the larva occurred between these instar stages. The highest growth ratio, with respect to head capsule and larval length, was 1.35 and 1.34 between the fourth and fifth instar.